New geopolitical realities of future civilization - Danilov, Alexander N. (Journal of the Belarusian State University. Sociology, 2019)
This research paper analyses a complex geopolitical situation of global instability that developed in the world at the end of the second decade of the 21st century, connected with the consequences of the collapse of the Soviet Union, the formation of new ideals of civilization development. It explains the dramatic results of the «parade of sovereignties», vulnerability of new integration projects. The frightening unpredictability of the global future and the stabilizing role of national states in world politics are described. The question is raised about who is going to define the new world order, whose templates it will be built on, what will become the basis for new geopolitical realities the basis of moral solidarity of mankind, the spiritual basis of the future civilisation, what ideal of the future world is supported and taken as a development guideline. In this thematic context, the author formulates the main lessons not mastered by the world power elite.